Social Relations and Everyday Consumption Rituals: Barriers or Prerequisites for Sustainability Transformation? - Boström, Magnus (Frontiers in Sociology, 2021)
Macro-institutional structures and consumerist culture force and urge people to reproduce unsustainable levels of consumption. A crucial role for sociology, the article argues, is to address theoretically and empirically the intersection between social relations and (over)consumption. The purpose with this article is to address how social relations are involved in both reproducing and challenging consumer culture. This is done by emphasizing the intersection of consumer culture and socially integrating everyday rituals and drawing on literature on both voluntary and involuntary (the pandemic) disruption of consumer practices. The Covid-19 pandemic brings unexpected opportunities to highlight this intersection, as the pandemic offers a window of opportunity for lifestyle change. The review shows there are important lessons about both challenges and opportunities, gained from both voluntary and involuntary disruption of consumer practices.